2023
DOI: 10.1111/ceo.14224
|View full text |Cite
|
Sign up to set email alerts
|

ROCK inhibitors in ophthalmology: A critical review of the existing clinical evidence

Abstract: Rho kinase (ROCK) inhibitors have emerged as a key therapeutic class of interest in ophthalmology over the last decade. Promising in vitro studies laid the foundations for the development of novel therapeutic agents that target the ROCK signalling pathway in ocular disease, with subsequent clinical trials supporting their use. Corneal endothelial disease, glaucoma, and vitreoretinal disease are the major pathologies in which ROCK inhibitors have been investigated to date. Ripasudil and netarsudil represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Approved in the US in 2017 and Europe in 2019 for reducing elevated IOP in primary open-angle glaucoma or ocular hypertension, it is administered once daily. [ 19 20 ] The drug has demonstrated consistent IOP reduction throughout the day and night and has been well-tolerated in multiple studies. [ 18 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approved in the US in 2017 and Europe in 2019 for reducing elevated IOP in primary open-angle glaucoma or ocular hypertension, it is administered once daily. [ 19 20 ] The drug has demonstrated consistent IOP reduction throughout the day and night and has been well-tolerated in multiple studies. [ 18 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Other ROCK inhibitors such as SNJ-1656 and Y-27632 are in various stages of clinical trials but are not yet commercially available. [ 18 19 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed for the activation of the ROCK pathway in corneal endothelial cells which cause increased cellular contractility, decreased cell proliferation, and reduced cell migration, ultimately leading to endothelial cell dysfunction. 7 , 37–39 …”
Section: The Rock Pathway In Corneal Endothelial Cellsmentioning
confidence: 99%
“…It has been approved in the United States since 2017, with subsequent authorization in the European Union in 2021. 7 , 39 …”
Section: Rock Inhibitors As Potential Therapeutics For Corneal Diseasesmentioning
confidence: 99%
“…The use of ripasudil for treating different subtypes of glaucoma, its long-term effects and adverse reactions, and maximum therapy tolerance, and the criteria for selecting target patients have been reported. Although ripasudil has been suggested as an effective monotherapy for uveitic glaucoma, most studies have indicated ripasudil as an adjuvant therapy to the first-line drugs for glaucoma [ 51 ]. So far, randomized controlled clinical trials of ripasudil monotherapy or existing standard therapy are lacking.…”
Section: Rock Inhibitors In Clinical Use For Glaucoma Therapymentioning
confidence: 99%